Reference intervals and percentiles for carotid-femoral pulse wave velocity in a healthy population aged between 9 and 87 years - Diaz, Alberto Alejandro (2018)
There is little information regarding age-related reference intervals (RIs) of carotidfemoral pulse wave velocity (cfPWV) for large healthy populations in South America. The aims of this study were to determine cfPWV RIs and percentiles in a cohort of healthy children, adolescents, and adults and to generate year-to-year percentile curves and body-height percentile curves for children and adolescents. cfPWV was measured in 1722 healthy participants with no cardiovascular risk factors (9–87 years, 60% men). First, RIs were evaluated for males and females through correlation and covariate analysis. Then, mean and standard deviation age-related equations were obtained for cfPWV using parametric regression methods based on fractional polynomials and age-specific (year-to-year) percentile curves that were defined using the standard normal distribution. Age-specific first, 2.5th, 5th, 10th, 25th, 50th, 75th, 90th, 95th, 97.5th, and 99th percentile curves were calculated. Finally, height-related cfPWV percentile curves for children and adolescents (<21 years) were established. After adjusting for age and blood pressure differences with respect to females, males showed higher cfPWV levels (6.60 vs 6.45 m/s; P < .01). Thus, specific RIs for males and females were reported. The study provides the largest database to date concerning cfPWV in healthy people from Argentina. Specific RIs and percentiles of cfPWV are now available according to age and sex. Specific percentiles of cfPWV according to body height were reported for people younger than 21 years.